Hybrid modelling in stratified decision support systems. II - Kolesnikov, A.; Yashin, A. (Mathematical Modelling and Analysis, 2001)
The paper studies the basic problems of Artificial Intelligence, such as integration of difference attributes of human intellect. For this purpose we have been created synergetic systems that are hybrid intelligent systems (HYIS). The paper shows the world of decision support problems and the world of modelling approaches evolution. The term ‘heterogeneous problem’ for decision support systems is discussed. Two models of interaction between the problems world and the methods world also the results of HYIS creating are discussed. The formalism of HYIS is introduced. Hibridinis sprendimų priėmimo sistemų modeliavimas. II Santrauka. Straipsnyje nagrinėjamos pagrindinės dirbtinio intelekto problemos, tame tarpe žmogaus intelekto savybių integravimas. Tuo tikslu yra sukurtos hibridinės protingos sistemos. Straipsnyje analizuojamos sprendinių priėmimo sistemos ir modelinių artinių vystymasis. Aptariamas sprendinių priėmimo sistemų heterogeniškumas. Apibrėžtas hibridinių protingų sistemų formalizmas. First Published Online: 14 Oct 2010